Analysis of the stability of water bodies to the action of destabilizing factors - Azarov, Sergii I.; Zadunaj, Oleksii S. (КНУБА : ІТГІП, 2018)
Methodical approaches to the assessment of ecological safety of ecosystems based on the establishment of a comprehensive indicator of the degradation of environmental components have been developed, which will allow us to assess non-additive properties of different-scale aquatic ecosystems. The analysis of methods for assessing the stability of water bodies to change the parameters of natural and anthropogenic regimes is carried out. Investigation of the nature of resistance of water bodies has revealed not only their desire for balance, but also a complex fight against regular and irregular (fluctuations) forces.
Keywords: ecosystem; ecosystem safety; stability; anthropogenic impacts; properties; parameters; environment; entropy; 504.4